Initial predictors for short-term prognosis in anti-melanoma differentiation-associated protein-5 positive patients - Qihua Yang; Tianfang Li; Xin Zhang; Kunlong Lyu; Shujun Wu; Yan Chen; Shengyun Liu; Zujiang Yu (Orphanet Journal of Rare Diseases, 2021)
Abstract Background Anti-melanoma differentiation-associated protein-5 (anti-MDA5) positive patients are characterized by the high mortality rate caused by interstitial lung disease (ILD). We conducted a retrospective study to summarize the clinical features and identify the initial predictors for death in anti-MDA5 positive patients. Methods We designed a retrospective cohort of anti-MDA5 positive patients. The demographic and clinical data recorded on first admission, as well as the outcomes during the first six months follow-up, were collected. Predictors of rapidly progressive ILD (RPILD) and poor outcomes were calculated using logistic regression models and Cox proportional hazard regression models, respectively. Results A total of 90 anti-MDA5 positive patients were included in this study. Eighty-one (90%) patients presented ILD on admission and 35 (38.9%) patients developed RPILD subsequently. During the first six months of follow-up, 22 (24.4%) patients died of respiratory failure at an average time of 6.6 ± 5.9 weeks. Factors including disease duration < 2 months (OR 6.1, 95% CI 1.7–22.4, P = 0.007), serum ferritin ≥ 1500 ng/ml (OR 12.3, 95% CI 3.1–49.6, P < 0.001), CRP ≥ 13 mg/L (OR 4.6, 95% CI 1.3–16.9, P = 0.021) and total GGO score ≥ 4 (OR 6.3, 95% CI 1.8–21.9, P = 0.003), were identified as independent predictors for RPILD. Cox regression model showed that total CT GGO score ≥ 4 (HR 4.8, 95% CI 1.3–17.9, P = 0.020), KL-6 > 1600 U/ml (HR 3.7, 95% CI 1.5–9.1, P = 0.004) and CRP > 5.8 mg/L (HR 3.7, 95% CI 1.0–12.8, P = 0.044) were poor prognostic risk factors, however initial combined treatment (HR 0.3, 95% CI 0.1–0.8, P = 0.019) predicted good prognosis in anti-MDA5 positive patients. Conclusion Anti-MDA5 positive patients demonstrated a high prevalence of ILD on admission, leading to a high short-term mortality rate. Higher total GGO score, higher levels of initial KL-6 and CRP predict poor outcome in anti-MDA5 positive patients. However, initial intensive treatment may improve the prognosis.